THE IMPACT OF THE WORK OF NOVICE TRANSLATORS ON THE QUALITY OF THE TRANSLATION - Puspani, Ida Ayu Made (Lingual Journal of Language and Culture, 2019)
This article aims at finding out the impact of the translation product and its readability conducted by the fourth semester students of the English Department Faculty Arts Udayana University 2017. The study was conducted by investigating the students` work on English-Indonesian translation class. There were 40 students as the participants, and they were given task to translate text from English into Indonesian. The results show that there were many distorted meaning of the SL in the translation, this is due to the lack of the ability of the students in understanding the meanings, such as contextual meaning and connotative meaning though they were given basic theory of translation, and how the source language English is different from the target language in terms of linguistics as well as cultural background. Keywords: novice .translator, impact, quality